Kajian Perilaku Masyarakat Pesisir yang Mengakibatkan Kerusakan Lingkungan (Studi Kasus di Pantai Kuwaru, Desa Poncosari, Kecamatan Srandakan, Kabupaten Bantul, Provinsi DIY) - Zulmiro Pinto (Jurnal Wilayah dan Lingkungan, 2015)
Coastal area is a transition area between sea and land. Coastal area development is influenced by the pressures of human activities occupying both areas. The condition is illustrated in Kuwaru Beach, Bantul District. Kuwaru Beach has a unique nature formed by pine tree lines and cheap culinary stalls around. However, the human behavior might have endangered its preservation due to illegal logging. The aim of this study was to examine the behavior of coastal communities associated with the environmental damage in KuwaruBeach and its impact on social and economic livelihood. A mixed method was applied by using sequential explanatory design. Selection of the sample was completed by purposive sampling on government and fishermen groups. The results showed that the behavior of the coastal communities has to lead to the environmental degradation. This research also found that the people's behavior is really influenced by the low education level and low awareness of the coastal region of Kuwaru Beach. The local government should work together with the local communities to conserve Kuwaru Beach from the man made environmental damage.